Relationship between Brand Experience, Brand Personality, Consumer Satisfaction, and Consumer Loyalty of DSSMF Brand - Kwong, Margie Zerlina; Candinegara, Ivan (iBuss Management, 2014)
PT XYZÂ  is one of the market leaders of Indonesiaâs tobacco market with domination in almost all segments of cigarette. However, PT XYZ is still considered unsuccessful in capturing the market of Full Flavor Machine Made Cigarette (known as SKM FF). This is proven by insignificant performance of DSSMF as PT XYZâs product under SKM FF segment, especially in Javanese market. This research is aimed to analyze the relationship of brand experience, brand personality, consumer satisfaction, and consumer loyalty of DSSMF. Furthermore, this research attempts to examine the role of brand personality as mediating variable between DSSMF brand experience and consumer loyalty. This research usedÂ  simple random sampling method. MoreoverÂ  simple and multiple linear regressions wereÂ  used as themethods of data-analysis. In gathering the data, the writers used online questionnaire with DSSMF consumers domiciled in Java as the targeted respondents and successfully gathered 94 respondents. These research findings indicate that consumer satisfaction is the only variable significantly impacting DSSMF consumer loyalty. Brand experience and brand personality variables are found to be insignificant to consumer loyalty of DSSMF. Consequently, brand personality is proven not to be the mediatingÂ  variable between brand experience and consumer loyalty of DSSMF. Â Keywords: Brand experience, brand personality, consumer satisfaction, consumer loyalty.